2010
DOI: 10.1039/b9nr00434c
|View full text |Cite
|
Sign up to set email alerts
|

Lasing in self-assembled microcavities of CdSe/CdS core/shell colloidal quantum rods

Abstract: Colloidal semiconductor quantum rods have demonstrated many advantageous properties as light emitters such as high quantum yield, tunable emission wavelength, and polarized emission. This makes them an interesting optical gain material for laser applications. We report room-temperature gain lifetimes in core/shell CdSe/CdS quantum rods exceeding 300 ps, and show that the long gain lifetimes result from the significant reduction of Auger recombination in our quantum rods, even though the electrons are delocaliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
141
0
2

Year Published

2011
2011
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 124 publications
(145 citation statements)
references
References 29 publications
2
141
0
2
Order By: Relevance
“…On contrary, the low PL QY in the above-mentioned other materials, especially the bulk polycrystalline fi lms, implies fast nonradiative recombination, thus more unfavorable heat will be generated, which plagues their optical properties and complicates thermal manage ment for device operation. [ 2,6 ] On the other hand, the rapid nonradiative Auger recombination occurring at high excitation intensities has been recognized to be the main channel dissipating the population inversion in QDs, [ 1,34 ] thus hindering the optical amplifi cation. To explore Auger recombination in these CsPbBr 3 IPQDs, the excitation intensity-dependent time-resolved PL measurements were performed on CsPbBr 3 IPQDs in solution (see details in Experimental Section).…”
Section: Doi: 101002/adma201503573mentioning
confidence: 99%
“…On contrary, the low PL QY in the above-mentioned other materials, especially the bulk polycrystalline fi lms, implies fast nonradiative recombination, thus more unfavorable heat will be generated, which plagues their optical properties and complicates thermal manage ment for device operation. [ 2,6 ] On the other hand, the rapid nonradiative Auger recombination occurring at high excitation intensities has been recognized to be the main channel dissipating the population inversion in QDs, [ 1,34 ] thus hindering the optical amplifi cation. To explore Auger recombination in these CsPbBr 3 IPQDs, the excitation intensity-dependent time-resolved PL measurements were performed on CsPbBr 3 IPQDs in solution (see details in Experimental Section).…”
Section: Doi: 101002/adma201503573mentioning
confidence: 99%
“…The magnitude of this optical gain lifetime is comparable with values determined for coreshell quantum rods which have been specifically designed to suppress the rate of Auger recombination. [42] Further investigations are underway to understand the role of the host matrix and the nature of the QD heterostructure in this enhanced Auger lifetime. effective gain coefficient, through the variable stripe (VSL) technique, [29] indicates a maximum of approximately 179 cm −1 for the 245 nm thick sample (Figure 4b and d).…”
Section: Linear and Nonlinear Absorption Characteristicsmentioning
confidence: 99%
“…[ 9 ] The ensuing reduced spatial overlap between the CdSe electron and hole wavefunctions is expected to yield suppressed Auger recombination rates, as was previously observed in a related system of CdSe seeded CdS nanorods exhibiting relatively long biexciton lifetimes of ∼ 300 ps. [ 10 ] While it has been suggested that CdSe seeded CdS nanotetrapods hold promise as good NC-based optical gain materials, [ 9 , 11 ] however, ASE from such structures has to the best of our knowledge not yet been demonstrated. In this work we synthesize and incorporate ZnS overcoated CdSe seeded CdS nanotetrapods into a solvent resistant and thermally stable sol-gel derived silica matrix, and demonstrate room temperature ASE from the resulting nanotetrapod-silica composites.…”
Section: Doi: 101002/adma201200121mentioning
confidence: 99%